A Century of Premiers - Leonard, D. author. aut Link
VIII, 391 p.
Keywords: During the course of the Twentieth Century, nineteen men and one woman - from Robert Cecil, Third Marquis of Salisbury to Tony Blair - have occupied the post of Prime Minister of the United Kingdom.